Analisis Dampak Tehnologi Informasi dan Komunikasi (TIK) dalam Meningkatkan Kinerja Pegawai pada Koperasi Pegawai Republik Indonesia (KPRI) “Bung” Lldikti Wilayah IX Sulawesi - Bambang Suharto; Milka Pasulu; Yusram Adi (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
Analysis of the Impact of Technology, Information and Communication (ICT) in Improving Employee Performance at the Republic of Indonesia Civil Servant Cooperative (KPRI) "Bung" LLDIKTI Region IX Sulawesi. Thesis for the Management Study Program at the Indonesian Education Institute of Management Science College (STIM-LPI) Makassar. Supervised by Dr. Milka Pasulu, S.E., M.Si and Dr. Yusram Adi, S.E., M.Sc This research aims to determine the impact of information and communication technology (ICT) in improving employee performance at the Republic of Indonesia Civil Servant Cooperative (KPRI) "Bung" LLDIKTI Region IX Sulawesi. This research was conducted using data collection through direct observation and interviews; The data collection methods used were interviews and direct observation. is based on qualitative data, where this research is subjective. The sample in this study was the administration section, and the manager of the Republic of Indonesia Employees Cooperative (KPRI) "Bung" LLDIKTI Region IX Sulawesi. The data analysis methods used are narrative analysis and discourse analysis. The results of this research show that information and communication technology (ICT) has a significant impact on improving employee performance.